Report of the committee on education and labor pursuant to S.Res.266 (74th congress). A resolution to investigate violations of the right of free speech and assembly and interference with the right of labor to organize and bargain collectively. Violations of free speech and rights of labor. Senate, 76th congress, 1st session (Washington, 1939)
Report no. 6, part 3. Industrial munitions. March 20 (legislative day March 16), 1939. With ills.